1977
DOI: 10.1007/bf00041135
|View full text |Cite
|
Sign up to set email alerts
|

Plate waves in Hadamard materials

Abstract: The dispersion equation for elastic waves of small amplitude in a pre-stressed plate of restricted Hadamard material is derived and its solutions are investigated in detail. The implications for stability are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Focusing on neo-Hookean solids (2.23) they showed that the critical stretches are λ cr = 0.666 for tangential equibiaxial compression (λ 1 = λ, λ 2 = λ −2 , λ 3 = λ), λ cr = 0.544 for plane strain compression (λ 1 = λ, λ 2 = λ −1 , λ 3 = 1), and λ cr = 0.444 for normal equibiaxial compression (λ 1 = λ, λ 2 = λ −1/2 , λ 3 = λ −1/2 ). Theirs was a static stability analysis, later also included in a wider dynamical context by Flavin [28], Willson [29], Chadwick and Jarvis [30], Dowaikh and Ogden [12], and , where σ 0 is the real root of σ 3 + σ 2 + 3σ − 1 = 0 (σ 0 = 0.2956). Clearly, in the examples of plane strain and equi-biaxial strain above, the squared wave speed increases when λ increases and decreases when λ decreases.…”
Section: Example: Compressive Stressesmentioning
confidence: 99%
“…Focusing on neo-Hookean solids (2.23) they showed that the critical stretches are λ cr = 0.666 for tangential equibiaxial compression (λ 1 = λ, λ 2 = λ −2 , λ 3 = λ), λ cr = 0.544 for plane strain compression (λ 1 = λ, λ 2 = λ −1 , λ 3 = 1), and λ cr = 0.444 for normal equibiaxial compression (λ 1 = λ, λ 2 = λ −1/2 , λ 3 = λ −1/2 ). Theirs was a static stability analysis, later also included in a wider dynamical context by Flavin [28], Willson [29], Chadwick and Jarvis [30], Dowaikh and Ogden [12], and , where σ 0 is the real root of σ 3 + σ 2 + 3σ − 1 = 0 (σ 0 = 0.2956). Clearly, in the examples of plane strain and equi-biaxial strain above, the squared wave speed increases when λ increases and decreases when λ decreases.…”
Section: Example: Compressive Stressesmentioning
confidence: 99%
“…We exclude consideration of the special case where a = 0, when the material is a 'restricted Hadamard material' [7,8,9,10]. Then, assuming a = 0, it may be shown [4,5] that in order for the Strong Ellipticity conditions to hold, the following inequalities must be valid:…”
Section: Basic Equations 21 Hadamard Materialsmentioning
confidence: 99%